Geometric morphometrics of the wings of Amazonian species of Melipona (Illiger, 1806) (Hymenoptera: Apidae) - Galaschi-Teixeira, Juliana Stephanie; Veiga, Jamille Costa; Tavares, Valéria Da Cunha; Imperatriz-Fonseca, Vera Lucia (Zootaxa, 2024)
Identifying and classifying species of stingless Neotropical bees is not a trivial task and requires the help of taxonomists and substantial study and training time. Also, there is a lack of taxonomically useful characters to differentiate among the megadiverse Neotropical group of stingless bees, and to recognize variation. Based on that, we have been testing alternatives to a character-based, efficient taxonomic determination of stingless bees, and herein we performed exploratory analyses of wing shape variation using geometric morphometrics. Thus, we built a data set of photographs of the right anterior wing of 1628 individuals belonging to 11 species in the genus Melipona (Illiger 1806) taken from collection material deposited in entomological collections. We then conducted a Procrustes analysis, followed by a Principal Component Analysis (PCA) and by a Canonical Variable Analyses (CVA). The two first principal components of the PCA accounted for 68% of the variation of the wing shape, and the ordination displayed by the first component separated species of the subgenus Melikerria from the others. In the CVA, the first two canonical axes explained 88% of the wing shape variation found among species, and Melikerria appears as a separate group, apart from the other subgenera in the first canonical axis. Along the second axis species belonging to Eomelipona and Michmelia, and among the Michmelia species, and its species group fuliginosa formed well-separated clusters. The wing shape variation of Melipona supports the recognition of subgenera as currently proposed for Melipona.